The Effect of Academic Supervision on Teacher’s Performance - Hartati, Sry (PPSDP International Journal of Education, 2024)
Academic supervision is assistance provided by the school principal which aims to develop the abilities of teachers and other school personnel so that educational goals can be achieved. School principals are expected to be able to carry out academic supervision optimally and objectively in conducting assessments so that supervision can have an impact on improving teacher performance. This research aims to determine the effect of academic supervision on teacher performance. This type of research is literature study research using 30 journals as study material. The stages in writing a literature study include topic selection, literature search, opinion development, literature survey, literature criticism, and writing a review. The results of the research state that there is an influence of academic supervision on teacher’s performance, especially in managing learning. The more optimal the implementation of academic supervision, the higher the teacher’s performance will be.